A HISTÓRIA SOCIAL DA FOTOPINTURA CABOCLA NO SERTÃO DE PITANGA, 1950 A 1975 - Guimarães, Valdir Machado (2014)
This research aims to study the photopaintings in caboclas central region of Paraná, in the period from 1950 to 1975. To this end, we have selected as object of analysis, a set of images of families of Pitanga and Manoel Ribas, where used interviews with the depicted or their descendants, in the search for unveiling the various possibilities of interpretations which affect this imagery treatment. The work is based on a theoretical framework that privileges the reflection on cultural practices that surrounded this product in that region, in the search for focus on the universe of their imaginary systems, their historical appropriations, reinserting the local aesthetic differences, inside the fotopintor mediation in the trace of the spaces that influence these images, as a relevant scenario of the regional context. The photopaintings are objects of historical studies, which allow thinking the perpetuation, the perception of imagery familiar sight, the representations, environmental sensitivities in the articulation of family memory and size of establishment of the framework of Visuality present in these pictures that have been highlighted in this dissertation.